Nutrients Recovery during Vermicomposting of Cow Dung, Pig Manure, and Biochar for Agricultural Sustainability with Gases Emissions - Syed Turab Raza; Bo Zhu; Jia Liang Tang; Zulfiqar Ali; Raheel Anjum; Hamidou Bah; Hassan Iqbal; Xiao Ren; Rida Ahmad (Applied Sciences, 2020)
An experimental vermicomposting system was established in purple soil present in Sichuan Basin, China. The purpose of vermicomposting (VC) was to recycle and manage organic waste materials; for instance, animal manure and crop residues are present in great quantity. A particular use of earthworms for VC is a valuable method for retrieving essential plant nutrients. Experimental vermicomposting followed by monitoring was conducted for two months in summer with an interval of fifteen days. Four treatments, COM (compost without earthworms), VCM (using cow manure), VPM (through pig manure), and VBC (using biochar), were applied with agricultural wastes such as rapeseed and wheat straw in combination with cow dung, pig manure, and biochar, respectively. One-way analysis of variance (ANOVA) was used to statistically analyze and interpret the nutrient change among different treatments. Post hoc analysis was done using Tukey’s test. The experimental vermicomposting results revealed that VCM gives increased plant nutrients with a minimum C: N ratio (from 22.13 to 14.38) and a maximum increase in nitrogen concentrations (1.77 to 29.15 g kg−1). A significant decrease in ammonia volatilization was observed in the order VCM > VBC > VPM when compared to COM. It was experimentally established that vermicomposting is the most suitable method for converting organic waste into nutrient-rich fertilizer with the least environmental pollution load.